Effects of a short and intensive transcranial direct current stimulation treatment in children and adolescents with developmental dyslexia: A crossover clinical trial - Battisti, Andrea; Lazzaro, Giulia; Costanzo, Floriana; Varuzza, Cristiana; Rossi, Serena; Vicari, Stefano; Menghini, Deny (Frontiers in Psychology, 2022)
Developmental Dyslexia (DD) significantly interferes with children’s academic, personal, social and emotional functioning. Nevertheless, therapeutic options need to be further validated and tested in randomized controlled clinical trials. The use of transcranial direct current stimulation (tDCS) has been gaining ground in recent years as a new intervention option for DD. However, there are still open questions regarding the most suitable tDCS protocol for young people with DD. The current crossover study tested the effectiveness of a short and intensive tDCS protocol, including the long-term, as well as the influence of age and neuropsychological processes at baseline on reading improvements. Twenty-four children and adolescents with DD were randomly assigned to receive active tDCS during the first slot and sham tDCS during the second slot or vice versa. Five consecutive daily sessions of left anodal/right cathodal tDCS set at 1 mA for 20 min were administered over the parieto-occipital regions. Reading measures (text, high frequency word, low frequency word and non-word lists) and neuropsychological measures (visual-spatial and verbal working memory, phoneme blending, and rapid automatized naming tasks) were collected before, immediately after, 1 week and 1 month later the treatment. Our results showed that only the active tDCS condition improved non-word reading speed immediately after and 1-month later the end of the treatment compared with baseline. In addition, the improvement in non-word reading speed was significantly correlated with age and with neuropsychological measures (verbal working memory and phoneme blending) at baseline but only in the active tDCS condition. The current crossover study contributed to enforce previous effects of tDCS, including long-term effects, on non-word reading speed and to understand the effect of age and neuropsychological processes on reading outcomes. Our findings showed that tDCS could be a low-cost and easy-to-implement treatment option with long-term effects for children and adolescents with DD.